Propagation and nanofocusing of infrared surface plasmons on tapered transmission lines: Influence of the substrate - Sarriugarte, P. (2012)
We study the propagation of mid-infrared surface plasmons on non-tapered and tapered two-wire transmission lines on Si and CaF 2 substrates, the two materials representing substrates with large and small refractive index, respectively. A comparative numerical study predicts a larger effective wavelength and an increased propagation length (i.e. weaker damping) for the CaF 2 substrate. By near-field microscopy we image the near-field distribution along the transmission lines and experimentally verify surface plasmon propagation. Amplitude- and phase-resolved near-field images of a non-tapered transmission line on CaF 2 reveal a standing wave pattern caused by back-reflection of the surface plasmons at the open-ended transmission line. Calculated and experimental near-field images of tapered transmission lines on Si and CaF 2 demonstrate that for both substrates the mid-IR surface plasmons are compressed when propagating along the taper. Importantly, the nanofocus at the taper apex yields a stronger local field enhancement for the low-refractive index substrate CaF 2. We assign the more efficient nanofocusing on CaF 2 to the weaker damping of the surface plasmons.